Usability Testing of an Interoperable Computerized Clinical Decision Support Tool for Fall Risk Management in Primary Care - Shear, Kristen; Rice, Hannah; Garabedian, Pamela M.; Bjarnadottir, Ragnhildur; Lathum, Nancy; Horgas, Ann L.; Harle, Christopher A.; Dykes, Patricia C.; Lucero, Robert (Applied Clinical Informatics, 2023)
Background Falls are a widespread and persistent problem for community-dwelling older adults. Use of fall prevention guidelines in the primary care setting has been suboptimal. Interoperable computerized clinical decision support systems have the potential to increase engagement with fall risk management at scale. To support fall risk management across organizations, our team developed the ASPIRE tool for use in differing primary care clinics using interoperable standards.Objectives Usability testing of ASPIRE was conducted to measure ease of access, overall usability, learnability, and acceptability prior to pilot .Methods Participants were recruited using purposive sampling from two sites with different electronic health records and different clinical organizations. Formative testing rooted in user-centered design was followed by summative testing using a simulation approach. During summative testing participants used ASPIRE across two clinical scenarios and were randomized to determine which scenario they saw first. Single Ease Question and System Usability Scale were used in addition to analysis of recorded sessions in NVivo.Results All 14 participants rated the usability of ASPIRE as above average based on usability benchmarks for the System Usability Scale metric. Time on task decreased significantly between the first and second scenarios indicating good learnability. However, acceptability data were more mixed with some recommendations being consistently accepted while others were adopted less frequently.Conclusion This study described the usability testing of the ASPIRE system within two different organizations using different electronic health records. Overall, the system was rated well, and further pilot testing should be done to validate that these positive results translate into clinical practice. Due to its interoperable design, ASPIRE could be integrated into diverse organizations allowing a tailored implementation without the need to build a new system for each organization. This distinction makes ASPIRE well positioned to impact the challenge of falls at scale.
Keywords: usability testing; clinical decision support; falls; primary care